2013
DOI: 10.1038/onc.2013.333
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 is required for tumorigenesis in a mouse model of intestinal cancer

Abstract: The epigenetic regulator BMI1 is upregulated progressively in a wide variety of human tumors including colorectal cancer. In this study, we assessed the requirement for Bmi1 in intestinal tumorigenesis using an autochthonous mouse model in which Apc was conditionally ablated in the intestinal epithelium. Germline mutation of Bmi1 significantly reduced both the number and size of small intestinal adenomas arising in this model, and it acted in a dose-dependent manner. Moreover, in contrast to wildtype controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…These treated animals (here called Braf/Pten) develop metastatic melanomas (Dankort et al 2009;Damsky et al 2011). We crossed a Bmi1 conditional allele (Maynard et al 2014 into this Braf/Pten model and confirmed that topical 4-OHT application yielded efficient recombination of the Bmi1 allele in the skin (Supplemental Fig. S6A).…”
Section: Bmi1 Loss In Vivo Impedes Melanoma Metastasis Formationmentioning
confidence: 86%
See 3 more Smart Citations
“…These treated animals (here called Braf/Pten) develop metastatic melanomas (Dankort et al 2009;Damsky et al 2011). We crossed a Bmi1 conditional allele (Maynard et al 2014 into this Braf/Pten model and confirmed that topical 4-OHT application yielded efficient recombination of the Bmi1 allele in the skin (Supplemental Fig. S6A).…”
Section: Bmi1 Loss In Vivo Impedes Melanoma Metastasis Formationmentioning
confidence: 86%
“…BRaf CA ;Pten ex5lox and Tyr::CreER mice (Jackson) were crossed to BMI1 fl/fl mice (Maynard et al 2014). Localized tumors were induced with 1 µL of 8.3mg/mL 4-OHT (70% Z-isomer; Sigma) in ethanol vehicle.…”
Section: Mouse Colony and Melanoma Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation of the polycomb complex oncogene B lymphoma Mo-MLV insertion region 1 homologue (Bmi1) dose-dependently reduced both the number and the size of small intestinal adenomas in a conditional APC knockout model. The Arf tumour suppressor, a target of Bmi1 epigenetic silencing, was upregulated in such tumours and is required for the induction of both p53 and apoptosis observed because of Bmi1 deficiency [51].…”
Section: Cancermentioning
confidence: 99%